Mapping glutamate in subcortical brain structures using high-resolution GluCEST MRI - Cai, Kejia (2013)
In vivo measurement of glutamate (Glu) in brain subcortex can elucidate the role these structures play in cognition and neuropsychiatric disorders. However, accurate quantification of Glu in subcortical regions is challenging. Recently, a novel MRI method based on the Glu chemical exchange saturation transfer (GluCEST) effect has been developed for detecting brain Glu in millimolar concentrations. Here, we use GluCEST to map Glu distributions in subcortical structures of the human brain (e.g. amgydala, hippocampus). Overall, GluCEST was ~40% higher in gray matter than in white matter. Within the subcortical gray matters, amygdala showed the highest GluCEST contrast. Utilizing MR spectroscopic data, In vivo GluCEST detection sensitivity (~0.8% per mM) in subcortical gray matters was evaluated and consistent to the previously reported values. In general, the GluCEST map approximates the Glu receptor distribution reported in previous Positron Emission Tomography (PET) studies. These findings suggest that high-resolution GluCEST MRI of subcortical brain structures may prove to be a useful tool in diagnosis brain disorders or treatment responses.